In vitro bioprospecting of rhizospheric fungi associated to cactus (Opuntia cochenillifera) to plant growth promotion - Silva, João Manoel da (2022)
This study aimed to evaluate in vitro the plant growth promotion capacity of rhizospheric fungi from Opuntia cochenillifera. The isolates were submitted to phosphate solubilization, acetic acid-3-indole (AIA) production, antagonism against phytopathogens, and growth under water activity. All test results were subjected to statistical analysis. The studied isolates were able to solubilize phosphate, being F04 (Aspergillus sp.) and F05 (Coprinellus radians) the ones that presented the highest solubilization indices. As to produce AIA, F02 (Penicillium sp.) and F07 (Aspergillus sp.) were the most promising. All isolates could inhibit the growth of Colletotrichum sp. and Fusarium sp. Water restriction provided mycelial growth for all isolates. Therefore, these characteristics confer characteristics as growth promoters in plants.